Why Sources ? Empirical Rigour, Reflexivity, and Archiving in the Social Sciences and Humanities in African Studies - (:unkn) unknown (My University, 2020)
Sources: Materials & Fieldwork in African Studies has taken on a novel mission for a social sciences and humanities journal: to place field materials at the heart of the analysis. The journal aims to consider the empirical objects researchers produce—and more often co-produce—in their particular investigative context and using specific methods that facilitate theory-building.These materials are very diverse in nature. They may be public or private archives; old or recent; retrieved in libraries or collected in the field. They may comprise local writing (notebooks, letters, diaries, autobiographies, tracts, pamphlets, religious writings, etc.); excerpts from interviews, conversations, and life stories; notes, particularly from participant observation; maps, diagrams, and sketches by researchers or their interlocutors; knick-knacks, museum exhibits, and regalia; election posters, clothing, and campaign songs; photographs, films, audio and video recordings; excerpts from “grey” literature (reports, evaluations) and newspapers; data from the Internet and social media networks. Examples abound: always relating to an object of study, the research questions that are being developed and re-developed in relation to it, and the research conditions at the time.
Keywords: African Research